Image registration method for assessing 3D hip alignment and implant position during standing posture - Koichi KOBAYASHI; Shin KAI; Makoto SAKAMOTO; Yuji TANABE; Kunihiko TOKUNAGA; Izumi MINATO; Takashi SATO; Yoshio KOGA (Journal of Biomechanical Science and Engineering, 2014)
The range of motion (ROM) resulting from total hip arthroplasty (THA) depends on the relative orientation of the femoral and acetabular components, and malpositioning of components is a possible cause of several complications. The purpose of this study was to validate a 3-dimensional (3D) lower extremity alignment assessment system (3D LAAS) for the measurement of alignment of natural and implanted hip joints and implant position with respect to the target bone with the subject in a standing position. Sawbone femur and pelvis and femoral and acetabular components of a total hip arthroplasty system were used. Three spherical markers were attached to each sawbone and each component to define the local coordinate system. Outlines of the 3D bone models and component computer-aided design models were projected onto extracted contours of the femur, pelvis, and implants in calibrated frontal and oblique X-ray images. The 3D position of each model was recovered by minimizing the differences between projected outlines and contours. Mean absolute errors were less than 1.27 ± 0.79 mm and 0.99 ± 0.52° for femur and pelvis, 1.64 ± 0.66 mm and 1.54 ± 0.39° for femoral and acetabular components, 1.58 ± 0.29 mm and 1.75 ± 0.69° for femur and femoral component, and 1.51 ± 0.49 mm and 1.24 ± 0.14° for pelvis and acetabular component, indicating that the 3D LAAS is applicable to measure the alignment of natural and implanted hip joints and implant position after THA.